Slovak Republic : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Slovakia is highly vulnerable to the war in Ukraine, given its geographical proximity, heavy reliance on energy imports from Russia, and high integration into global value chains. The shock occurs against the backdrop of an incomplete recovery from the pandemic, with activity hampered by breakdowns in global supply chains and resurgent infection waves. Growth is projected to slow to 2.2 percent and inflation to surge to over 10 percent in 2022, with sizable downside risks amidst exceptionally large uncertainty.